A 7.08-kW YAG/Nd:YAG/YAG Composite Ceramic Slab Laser with Dual Concentration Doping - Mi Li; Hao Hu; Qingsong Gao; Juntao Wang; Jian Zhang; Yingcheng Wu; Tangjian Zhou; Liu Xu; Chun Tang; Na Zhao; Peng Liu (IEEE Photonics Journal, 2017)
The theoretical design and experiment research on the YAG/Nd:YAG/YAG composite ceramic slab laser amplifier were conducted. The numerical analysis was used to obtain the design of YAG/Nd:YAG/YAG composite ceramic slab. A high optical quality composite ceramic slab with two different doping concentrations was fabricated successfully. The double-pass extracted power in composite ceramic slab laser amplifier reached 7.08 kW, and the optical-to-optical conversion efficiency increased to 39.2% under the total diode pump power of 18.06 kW. The depolarization of single-pass transmission was about 3.2% and the peak and valley of the transmission wave-front distortion among the center 26.1-mm region in the width direction of the laser slab was less than 0.5 μm at the double-pass extracted power of 7.08 kW.